(x-y)/8 = x/9
(x+y)/10 = x/9
solving for y will yield:
x-y = (x*8)/9
y = x/9
9y = x
John got in advance x dollars so ---> 9y
How are you equating
x-y/8 = x/9?
You are equating money she has ( X -y) / the number of hours she worked to hourly wage?
Lets assume Mary got 180 dollars and John got 180 dollars.
they worked for a total of 18 houres.
so the average pay per hour of both of them is 360/18 = 20
since Mary got 180/8 = 22.5 per hour and John got 180/10 = 18 per hour Mary gave John (2.5*8) dollars, this is y !!! she now has 180 (i.e x) - 20 (i.e y) = 160/8 = 20 per hour.
John got y (i.e 2.5*8) dollars and now he has 180 (i.e x) + 20 (i.e y) = 200/10 = 20 per hour
9y = x
20*9 = 180
its much easier to plug in smart numbers.
$80 each person
j = $8 an hour
m = $10
In order for j and m to have the same amount of money per hour, 10+8 / 2 = $9 per hour for both ppl.
m must give 1 dollar. y=1
therefore, john receives $9 dollars an hour, as does M. $9/hr in terms of y is 9y.
You tried your best and you failed miserably. The lesson is 'never try'. -Homer Simpson